EFFECT OF COMPENSATION, COMMUNICATION AND SPIRITUALITY AT WORK ON THE PERFORMANCE OF THE TURNOVER INTENTION AS AN INTERVENING VARIABLE - Sumiati, Sumiati Sumiati (Archives of Business Research, 2018)
The purpose of this study are (1) To determine and analyze the effect of compensation towards employee turnover intention. (2) To determine and analyze the influence of compensation on employee performance. (3) To determine and analyze the effect of communication on the employee turnover intention. (4) To determine and analyze the effect of communication on employee performance. (5) To determine and analyze the influence of spirituality in the workplace on employee turnover intention. (6) To determine and analyze the influence of spirituality in the workplace on employee performance. (7) To determine and analyze the effect on the performance of the employee turnover intention. The research approach used in this study is a quantitative research. This type of research is explanatory research using a survey method. The sample used in this study saturated or census sampling means that the number of samples as similar as to the number of population are 84. To further analyzed using the methods and analysis techniques Partial Least Square (PLS). The results showed that compensation, communication, and spirituality of the performance of employees have positive and significant influence, compensation and spirituality in the workplace against turnover intention have a negative impact significantly, the communication on turnover intention have a negative impact not significant and turnover intention of the performance have a negative impact not significant.